Pemanfaatan Lahan Pekarangan dalam Mendukung Ketahanan Pangan Rumah Tangga Melalui Metode Vertikultur - Ekawati; Rahmatullah Rizieq; Hery Medianto Kurniawan (Universitas Lancang Kuning, 2020)
One of the alternatives to mitigate the limitations of agricultural land in urban areas in an effort to produce family food is the use of yard with verticulture method. However, the partners of this community service activity were housewives in Permata Griya RT Residence 03/RW 019; most of them have not utilized their home yard for any productive and economically valuable activities through plant cultivation. This is caused by the limited land and partners’ knowledge about plant cultivation techniques. This community service activity aims to provide training and practice of narrow land utilization with verticulture method, arranging plants vertically using used tins and plastic bottles.. The service activity was conducted through lecture, discussion, and demonstration approach. The result of the activity impacted on the participants’ knowledge and insight: all participants knew cultivation techniques and make the growing media of verticulture mainly by using used goods